A study of school-based oral English assessment in rural secondary schools in Sandakan division, Sabah - Paramasivan A/L Sinnasamy (2007)
The purpose of this study was to determine the factors related t.o the implementation of School-based oral English assessment in rural secondary schools in Sandakan Division, Sabah. This study was aimed to find out the differences in the implementation of school-based oral English assessment based on selected demography factors. This study also aimed to find the level of English Langua.ge teachers' perception towards the implementation of school-based oral English assessment. This study went on further by identifying the relationship between the implementation of school-based oral English assessment with the influencing factors: content, function and perception of the teachers. A total of 56 respondents from 14 rural secondary schools from three rural areas under Sandakan Division were sam_pled and administered with structured questionnaires. Descriptive and inferential statistics were used for this study. It was found that there is no significant difference based on demography factors. It was also found the teachers have positive perception towards the implementation of school-based oral English assessment. It was found that the function factor has a strong correlation· ( r= .52IIJ with the implementation of school-based oral English assessment. Whereas the perception factor (r=.371) and the content factor (r=.366) have a medium strength correlation with implementation of school-based oral English assessment. Finally, it was found that the function factor was the most influencing factor followed by the perception factor towards the implementation of school-based oral English assessment. This study showed that the content factor was not an influencing factor to the implementation of school-based oral English assessment.